Rasio Pengukuran Return On Equity Dan Earnings Per Share Dalam Memprediksi Return Saham - Reza Octovian; Yoan Disti Fahira (STIE AUB Surakarta, 2022)
The capital market is an important indicator that will affect a country's economic growth rate because it can attract investors to invest. This study aims to identify return on equity and earnings per share in empirical research to predict stock returns in companies in the retail trade sector on the Indonesia Stock Exchange. The causality-type research method was formulated in this study with a quantitative analysis approach. The final sample involved 109 observational data on trade (retail) sector companies for 11 years. Data analysis using multiple regression techniques. The results of the study provide empirical evidence that return on equity (ROE) and earnings per share (EPS) are each capable of predicting stock returns either simultaneously or partially. The amount of contribution generated by Stock Returns originating from return on equity (ROE), and earnings per share (EPS) has a high contribution size of 59 percent.